Anisotropic mode excitations and enhanced quantum interference in quantum emitter-metasurface coupled systems. (1st September 2022) - Fang, Wei; Chen, Ying; Zeng, Yali; Ou, Congjie; Li, Gao-xiang; Yang, Yaping
Abstract: This study proposes a nanophotonic structure that supports quantum interference (QI) between orthogonal decay channels in multilevel quantum emitters within the framework of the quantum master equation. The Green functions of the electric field are obtained by applying boundary conditions in the presence of two-dimensional metasurfaces. We demonstrate distinct in-plane excitation features of the surface plasmon modes (SPMs) with the anisotropic metasurfaces tailored to conductivity components. In particular, we observed that the Purcell factor of transitions with orthogonal polarizations experiences unequal enhancements, owing to the anisotropic propagation of the SPMs. This property depends only on the anisotropy of the metasurfaces; thus, it is easily manipulated. Using this platform and considering experimentally achievable material parameters, we predict a strong interference effect in three-level quantum emitters. In principle, this enables the generation of maximum QI. Our study provides a method for realizing QI systems and has potential applications in highly integrated, tuneable quantum devices.